Mercado e devoção: um estudo sobre as transformações recentes na festa do Divino Pai Eterno em Trindade - Goiás - Rabelo, Cláudia Maria (2016)
The objective of this work is reflect about the theme Catholicism Popular before the neoliberalism installation process in Brazilian society. Focused on the connexion of Market and Devotion, analyzes the theme observing through the recent transformations in the feast of the Divine Eternal Father in Trindade, Goiás. In this context, seeks the answer of the question why does the religion in this contradictory world, mixture between Faith, Sacred and market. Then, it perceives that Religion remains because people search in the answers for your insecurity and anguish. The research reveals the confirmation of the Bourdieu’s thought (1998), the Religion exercises structuring, legitimating and justificating functions of the society and exercises social functions that legitimizes the arbitrary. This fact is reseach in Devotion of Divine Eternal Father in your recents transformations.